Impact of Open Distance Learning (ODL) on mathematics students at UiTM Perlis branch - Mahat, Norpah; Raseli, Siti Sarah; Nazihah, Adriana (Faculty of Administrative Science and Policy Studies, 2023)
The education systems around the world have been greatly affected by Covid-19 outbreak. Teaching and learning methods have been changed from traditional methods that set up face-to-face lectures in a classroom to online distance learning. The higher education institutions are moving to blended learning with elements of face-to-face provision, or hybrid learning where learning supports simultaneous face-to-face and online learning. Although the online distance education is convenient, there are some obstacles that students must overcome. Thus, the main objective of this study is to identify the main perceived impacts of Open Distance Learning (ODL) on UiTM Perlis for mathematics students. A questionnaire was distributed to Mathematics students at UiTM Perlis to explore and find out the problems that they have faced during ODL. Fuzzy Analytic Hierarchy Process was used to rank the factors that contribute and affects students during ODL. The Fuzzy Analytic Hierarchy Process (FAHP) is a method of Analytic Hierarchy Process (AHP) which is developed using fuzzy logic theory. There are nine steps in this method includes determination the goal, construct the hierarchical structure, pairwise comparison matrix, check for consistency, aggregated Fuzzy number of preferences, updated pairwise comparison matrix, weight vector calculation, defuzzification and final ranking. This study found that the greatest impact of ODL on UiTM Perlis Mathematics students is their “time spent learning”, followed by their sleeping patterns, student performance, engagement to learn and mental health. The results of this study will guide the policy makers of educational institutions to improve the achievement of online learning process to the next level more successfully.